Le voyage à Héliopolis : description des vestiges pharaoniques et des traditions associées depuis Hérodote jusqu'à l'Expédition d'Egypte - El-Banna, Essam Salah, (Recherches d'Archeologie de Philologie et d'Histoire ;, 2014)
"The city of Heliopolis in Egypt has always fascinated its visitors. Some recognized the residence of the famous magician-priests of the Phraraohs, those who gave their teachings to some great men of ancient Greece; others, the places of famous episodes of the Holy Scriptures; even others, some strange remains with miraculous virtues. This book gathers the descriptions of Heliopolis and its ruins by pilgrims, travelers, geographers and historians from different cultural backgrounds: Greeks, Romans, Muslims, Jewishs [sic], Christians of Orient and Occident. These testimonies, from the 5th century BC to the end of the 18th century AC, tell us about the appearance of the site and its monuments over the centuries, its history and above all, teh legends developed around this universal symbolic place" -- Page [4] of cover.